Narrativa oral : uma arte milenar - Blos, Anelise Toni (2007)
This research investigates the oral narratives: a millenary art. The study that took place in the school of Basic Education Arabutã in the Municipal District of Arabutã, Santa Catarina, Brazil, approaches the process, the factors, and the instances that interfered, determinated and also influenced the itineraries in relation to the theme as a way of socialize and interact while reading among students of different ages that are in the Fundamental Education and Secondary Education of the school. This research, that are based on studies linked with the Oral Narration, Education, History of Reading, and History of the Subject involved in the study tried to learn more about the narration of stories, in this work known as the telling of stories, helps the teachers in their pedagogical practice, questioning if this art can serve as a motivation for the pleasure of reading. Through the analyses and comparison of the statements in the questionnaires, and based on the presuppositions of the functional theory, it s looked for information with the test individuals about the experience with the oral narratives. Like this, it was possible to trace the profile of these individuals and to see their different ways of interacting with the oral. This exam also allowed the construction of a panorama capable of pointing the oral narratives in circulation, the ways of transmission, divulgation and socialization, the environment, the methods of changing histories, the practices adopted by the studied individuals and the diversity of competences in the studied school, the pedagogical practice of the teachers and the motivation for the pleasure of reading